Interventions for treating oral mucositis for patients with cancer receiving treatment - Clarkson, Jan E; Worthington, Helen V; Furness, Susan; McCabe, Martin; Khalid, Tasneem; Meyer, Stefan (Cochrane database of systematic reviews, 2010)
Treatment of cancer is increasingly effective but associated with short and long term side effects. Oral side effects, including oral mucositis (mouth ulceration), remain a major source of illness despite the use of a variety of agents to treat them. To assess the effectiveness of interventions for treating oral mucositis or its associated pain in patients with cancer receiving chemotherapy or radiotherapy or both. Electronic searches of Cochrane Oral Health Group and PaPaS Trials Registers (to 1 June 2010), CENTRAL via The Cochrane Library (to Issue 2, 2010), MEDLINE via OVID (1950 to 1 June 2010), EMBASE via OVID (1980 to 1 June 2010), CINAHL via EBSCO (1980 to 1 June 2010), CANCERLIT via PubMed (1950 to 1 June 2010), OpenSIGLE (1980 to 1 June 2010) and LILACS via the Virtual Health Library (1980 to 1 June 2010) were undertaken. Reference lists from relevant articles were searched and the authors of eligible trials were contacted to identify trials and obtain additional information. All randomised controlled trials comparing agents prescribed to treat oral mucositis in people receiving chemotherapy or radiotherapy or both. Outcomes were oral mucositis, time to heal mucositis, oral pain, duration of pain control, dysphagia, systemic infection, amount of analgesia, length of hospitalisation, cost and quality of life. Data were independently extracted, in duplicate, by two review authors. Authors were contacted for details of randomisation, blindness and withdrawals. Risk of bias assessment was carried out on six domains. The Cochrane Collaboration statistical guidelines were followed and risk ratio (RR) values calculated using fixed-effect models (less than 3 trials in each meta-analysis). Thirty-two trials involving 1505 patients satisfied the inclusion criteria. Three comparisons for mucositis treatment including two or more trials were: benzydamine HCl versus placebo, sucralfate versus placebo and low level laser versus sham procedure. Only the low level laser showed a reduction in severe mucositis when compared with the sham procedure, RR 5.28 (95% confidence interval (CI) 2.30 to 12.13).Only 3 comparisons included more than one trial for pain control: patient controlled analgesia (PCA) compared to the continuous infusion method, therapist versus control, cognitive behaviour therapy versus control. There was no evidence of a difference in mean pain score between PCA and continuous infusion, however, less opiate was used per hour for PCA, mean difference 0.65 mg/hour (95% CI 0.09 to 1.20), and the duration of pain was less 1.9 days (95% CI 0.3 to 3.5). There is weak and unreliable evidence that low level laser treatment reduces the severity of the mucositis. Less opiate is used for PCA versus continuous infusion. Further, well designed, placebo or no treatment controlled trials assessing the effectiveness of interventions investigated in this review and new interventions for treating mucositis are needed.